CSIG-20. EFFECT OF TUMOR-TREATING FIELDS (TTFIELDS) ON EGFR PHOSPHORYLATION IN GBM CELL LINES. (11th November 2019) - Luisa D'Angelo, Maria; Piffaretti, Deborah; Burgio, Floriana; Chiappini, Alessio; Marchi, Francesco; Reinert, Michael
Abstract: Glioblastoma (GBM) is the most common high grade and most devastating brain tumor among adults. About 50% of GBM express EGFR (epidermal growth factor receptor) and from these another 50% the mutated form EGFRvIII which is associated with a more aggressive disease and poorer prognosis. We have previously shown that expression of different status of EGFR in GBM cell lines drives the 5-ALA induced fluorescence downstream by influencing the rate-limiting enzyme heme oxygenase-1 (HO-1) probably via PI3K/Akt signalling. We demonstrated that 5-ALA-induced protoporphyrin IX (PpIX) fluorescence is pharmacologically influenced by adding different drugs such as deferoxamine (DFO) and tin-protoporphyrin (SnPP), which are an iron chelator of Fe 2+ and an inhibitor of HO-1 respectively, or genistein that promotes PpIX accumulation via functional repression of ABCG2 (ABC transporter G2). Our aim is to increase these pharmacological effects on PpIX fluorescence using tumor-treating fields (TTFields). TTFields, a new therapeutic technology for treating newly diagnosed or recurrent GBM, is able to suppress the growth of cancer cells destabilising microtubule elongation and increasing membrane permeability. Interestingly, TTFields, like as other destabilising drugs and compounds, is able to inhibit the phosphorylation of EGFR and subsequent downregulation of EGFR-induced signalling acting for example on the mechanism that regulate the HO-1 activity. Here, we investigate the effects of TTFields on glioma cells, with different EGFR status and consequently different PpIX fluorescence. Exposure to TTFields during or after pharmacological treatments may represent a novel strategy to block or diminish the phosphorylation of EGFR to ameliorate the visualization of PpIX fluorescence in patients where it is not enough to ensure a safe and precise removal of the tumor bulk. In fact, if a combination of TTFields and drug treatment should give the desired results, this strategy could be applied on patients before being subjected to surgical resection.